2022
DOI: 10.29219/fnr.v66.8050
|View full text |Cite
|
Sign up to set email alerts
|

Association between parental feeding practices and children’s dietary intake: a cross-sectional study in the Gardermoen Region, Norway

Abstract: Background Parental feeding practices may be important determinants for children’s diets. In Norway, few studies have assessed this association and to our knowledge, no studies have included fish as an outcome. Objective The purpose of this study was to explore the association between multiple parental feeding practices and children’s food intake. Design Parents (n = 111) of preschool children aged 1–5 years in the Gardermoen Region in Norway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In fact, more recent studies point out that a moderate level of parental control, such as "Monitoring" the consumption of unhealthy foods, is a strategy that impacts children's food consumption and is associated with maintaining adequate weight and healthy eating, including fruits and vegetables [30][31][32]. In this connection, these findings reinforce the parental feeding practice of "Monitoring" as a strategy that should be encouraged, as a way to control the consumption of less healthy foods by children and even to encourage the consumption of foods considered healthy [16,27].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, more recent studies point out that a moderate level of parental control, such as "Monitoring" the consumption of unhealthy foods, is a strategy that impacts children's food consumption and is associated with maintaining adequate weight and healthy eating, including fruits and vegetables [30][31][32]. In this connection, these findings reinforce the parental feeding practice of "Monitoring" as a strategy that should be encouraged, as a way to control the consumption of less healthy foods by children and even to encourage the consumption of foods considered healthy [16,27].…”
Section: Discussionmentioning
confidence: 99%
“…Parent-child interactions termed "food parenting" include feeding styles covering a wide range of feeding with the inclusion of emotions and parental feeding practices (PFP), which are specific strategies and actions (the "when, what, and how") [25]. It has been shown that childhood experiences resulting from PFP are correlated with dietary practices [26,27] as well as with the food preferences of adults [28]. Such PFP as encouraging eating in a supportive manner, modeling favorable eating behaviors, and eating meals together might favor healthy eating behaviors and greater diet quality [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, inadequate complementary feeding practices, including insufficient food or a balanced diet, can lead to malnutrition, weight loss, muscle wasting, and stunting in children (Ganesan et al, 2022). Furthermore, research by Mazza et al (2022) revealed that coercive control practices, including restrictive feeding practices, have been associated with unfavourable food intake and may contribute to malnutrition or wasting in children. Russell et al (2018) study results show that parents of preschoolers who were randomly allocated to a nutrition intervention used less food as a reward, less pressure to eat, and less child control than parents of preschoolers who had not participated in the nutrition intervention arm of the study.…”
Section: Yangmentioning
confidence: 99%